please could anyone explain this step ∫1/(2a)√(u) du = a²/3.?
u = (a² - x²)
- MorewoodLv 79 years agoFavorite Answer
That "a" is a constant and the integral is taken from u=0 to u=a. (That is from x=a to x=0, but "x" is irrelevant.)
By the constant and power rules for integrals:
∫1/(2a)√(u) du = [1/(2a)] u^(3/2) / (3/2) + C = u^(3/2) / (3a) + C
Substituting u=a (which gives a^(3/2)/(3a)+C=a²/3+C) and u=0 (which gives 0+C=C) and subtracting produces the required result.Source(s): Review your integration rules! http://www.alcyone.com/max/reference/maths/integra...
- D gLv 79 years ago
is the square root on the denominator or numerator
the equation in the integral is it 1/(2a * sqrt (u)) or is it